Pengembangan LKPD Berbasis PBL Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SMP Negeri 1 Tanjung Morawa - Saragih, Agnes Liska Rosadani; Hasratuddin Hasratuddin (International Forum of Researchers and Lecturers, 2024)
The purpose of this research was to produce a worksheet based on problem-based learning that would enhance students' ability to communicate mathematically when working with number pattern content. The quality of this LKPD refers to the effective aspect. This research uses a type of research and development (R&D) with a model developed by Borg & Gall. The subjects in this research were students in class VIII-5 of SMP Negeri 1 Tanjung Morawa with a total of 27 students. The object of this research is teaching materials in the form of PBL-based LKPD. Teacher response questionnaires, student response questionnaires, expert validation sheets, teacher interview question sheets, and tests of mathematical communication competence were the tools employed. Based on the research results, the effectiveness of LKPD can be seen from the achievement of learning completeness with an average individual learning completeness of 88 and for classical completeness of 96.3%. So the LKPD developed is declared